2021
DOI: 10.1016/s0140-6736(21)01326-x
|View full text |Cite
|
Sign up to set email alerts
|

From routine data collection to policy design: sex and gender both matter in COVID-19

Abstract: Vaccine equity is a growing concern of COVID-19 vaccination roll-outs and uptake globally. Gender has a role in vaccine uptake 1 but goes largely unrecognised in vaccine policies and programmes, undermining attempts to ensure equity. There is a wider gender blind spot that pervades national health responses to COVID-19 beyond vaccination, ranging from the way countries collect and report data to the commitments they make in pandemic health policies.Socially constructed gender norms can mean that women's access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…In this mini review of studies reporting efficacy and/or safety outcomes of vaccines included under COVAX, we found that women and men were equally represented in RCTs, whilst women (and healthcare workers) comprised the majority of participants in observational studies. Despite global calls for the routine disaggregation of COVID-19 data by sex/gender (59)(60)(61)(62), only two RCTs reported efficacy data by sex/gender, and none stratified safety data by sex/gender. Among the 34 included observational studies, 13 (38%) presented all sex/gender-disaggregated data (n =1 (3%) for efficacy and n = 12 (35%) for safety).…”
Section: Overall Summary Of Findingsmentioning
confidence: 99%
“…In this mini review of studies reporting efficacy and/or safety outcomes of vaccines included under COVAX, we found that women and men were equally represented in RCTs, whilst women (and healthcare workers) comprised the majority of participants in observational studies. Despite global calls for the routine disaggregation of COVID-19 data by sex/gender (59)(60)(61)(62), only two RCTs reported efficacy data by sex/gender, and none stratified safety data by sex/gender. Among the 34 included observational studies, 13 (38%) presented all sex/gender-disaggregated data (n =1 (3%) for efficacy and n = 12 (35%) for safety).…”
Section: Overall Summary Of Findingsmentioning
confidence: 99%
“…Interestingly, in covid-19 where men are more prone to a severe course, the use of antiandrogens in men have shown promising results on severity (47). Furthermore, in a review of health records in post-menopausal women with regular use of oestradiol, the fatality risk of covid-19 is reduced by more than 50% (48).…”
mentioning
confidence: 99%
“…That same article also covers older patients, finding that "older patients, and in particular, in female older patients, it has been reported a progressive functional decline in the immune systems" [11]. In some countries, differences in gender roles find women with "low autonomy, labour responsibilities, and unpaid care burdens were reasons for gendered barriers to vaccination that disadvantaged women" [12]. Others suggest hormone levels in both men and women impact vaccine tolerance [13].…”
Section: Introductionmentioning
confidence: 98%
“…There have been several articles which looked at sex and age differences of people who had experienced adverse events [10][11][12][13][14][15][16]. Some suggest women have stronger immune systems [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation